2020
DOI: 10.1080/22797254.2020.1738900
|View full text |Cite
|
Sign up to set email alerts
|

A novel fire index-based burned area change detection approach using Landsat-8 OLI data

Abstract: Change detection from multi-temporal remote sensing images is an effective way to identify the burned areas after forest fires. However, the complex image scenario and the similar spectral signatures in multispectral bands may lead to many false positive errors, which make it difficult to exact the burned areas accurately. In this paper, a novel-burned area change detection approach is proposed. It is designed based on a new Normalized Burn Ratio-SWIR (NBRSWIR) index and an automatic thresholding algorithm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 21 publications
2
37
0
2
Order By: Relevance
“…Vegetation indices were also necessary due to diversity of vegetation over the entire study area and the similarity of the burned vegetation response with those of croplands. Many research studies have argued that the burned indices improved the accuracy of burned area mapping [15,32,33].…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation indices were also necessary due to diversity of vegetation over the entire study area and the similarity of the burned vegetation response with those of croplands. Many research studies have argued that the burned indices improved the accuracy of burned area mapping [15,32,33].…”
Section: Feature Extractionmentioning
confidence: 99%
“…Change detection is one of the most important applications of RS and has been widely used for estimating burned areas using pre-and post-fire datasets [32]. In this study, image differencing was used as the change detection algorithm.…”
Section: Change Detectionmentioning
confidence: 99%
“…Remote sensing (RS) is one of the most important contact-free sensing means for Earth observation (EO) to extract relevant information about the physical properties of the Earth and environment system from spaceborne and airborne platforms. With the ever-growing availability of RS data sources from both satellite and airborne sensors on a large scale and even global scale, multimodal RS image processing and analysis techniques have been garnering growing attention in various EO-related tasks( Schmitt and Zhu, 2016 ), such as land cover change detection ( Liu et al, 2017 , Liu et al, 2019 ), disaster monitoring and management ( Zhu et al, 2019 , Liu et al, 2020 ), urban planning ( Weng, 2009 , Xie and Weng, 2017 ), mineral exploration ( Hong et al, 2019b , Siebels et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Engelbrecht et al (2017) proposed a Normalized Difference Alpha-Angle Index for burned area identification by using multi-polarisation C-band SAR. Liu et al (2020) proposed a new burned area change detection approach by using Landsat-8 OLI data based on the fire index and Otsu algorithm. More research on burned area mapping based on fire index can be found in (Chuvieco et al, 2002;Roteta et al, 2019;Woźniak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%